PERILAKU SMART NPC BERBASIS KOORDINASI MULTI AGENT MENGGUNAKAN FUZZY COORDINATOR - Tri Daryatni; Mochamad Hariadi; Ahmad Zainul Fanani (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2017)
Computer games are very popular today, not only children but also adults like to play games. Good computer game is a game that has the type of NPC (Non-Player Character) that similar to humans, and looks natural. To make the game more interesting requires proper coordination between the NPC and multi agent intelligent. Multi agent based Artificial intelligent game will feature a challenging and exciting, so that people who play games not only get a lesson and recreation but also will not feel quickly bored with the existing game. By using Fuzzy Coordinator will make coordination between the NPC and the Smart Agents stronger. Multi agent cooperation would control the health of each NPC. Agent will coordinate the NPC where the strong and the weak, where should resign or stay afloat, so the game will be a lot of challenges and not boring.